A circularly polarized photodetector based on triangular ferroelectric nanometer island structure and a preparation method thereof

CN122679706APending Publication Date: 2026-09-01ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610836326.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0004]然而,目前手性自旋电子学的发展仍面临着严峻的材料瓶颈

Benefits of technology

[0022] (1) This invention constructs a pn heterojunction of Nb-doped SrTiO3 substrate and Eu-doped BiFeO3 film as a photosensitive element. The built-in electric field effectively suppresses dark current and promotes the separation and transport of photogenerated carriers, realizing self-driven detection without external bias voltage, thus fundamentally reducing device power consumption. At the same time, by controlling the lattice through Eu doping and combining it with pulsed laser deposition (PLD) process parameters, the controllable fabrication of self-assembled triangular ferroelectric nanoisland crystal arrays is realized. This three-dimensional nanostructure significantly enhances the interaction between light and matter, and the chiral geometry of the triangular nanoislands and the BEFO intrinsic chiral spin splitting effect work synergistically to significantly enhance the spin selectivity response of the device to circularly polarized light, greatly improving the sensitivity and response speed of the detector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122679706A_ABST
    Figure CN122679706A_ABST
Patent Text Reader

Abstract

This invention proposes a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure and its fabrication method, belonging to the technical field of ferroelectric materials. It addresses the problems of traditional spintronic devices, such as reliance on external magnetic fields, low energy efficiency, complex structures, and insufficient sensitivity of existing circularly polarized photodetectors. The circularly polarized photodetector of this invention consists of a bottom electrode, a substrate, a ferroelectric layer, and a top electrode stacked sequentially from bottom to top. The substrate is an Nb-doped SrTiO3 substrate, and the ferroelectric layer is an Eu-doped BiFeO3 thin film. The Nb-doped SrTiO3 substrate and the Eu-doped BiFeO3 thin film form a p-n heterojunction. This invention achieves self-driven detection without an external bias voltage, effectively suppresses dark current, and significantly improves the axial selectivity response of circularly polarized light by utilizing the synergistic effect of the chiral geometry of the nanoislands and intrinsic spin splitting. The fabrication process is mature and facilitates large-scale integration applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of ferroelectric materials, and particularly relates to a photodetector. Background Technology

[0002] With the explosive growth of data in the information age, the pursuit of high-density, low-power, and ultra-high-speed storage and computing has become a consensus and an urgent need. Unlike traditional electronics, which only utilizes the charge property of electrons, spintronics utilizes both the charge and spin degrees of freedom of electrons to achieve information storage, transmission, and processing, and is considered a key cornerstone of next-generation information technology. However, traditional spintronics requires breaking the spacetime inversion symmetry to achieve spin manipulation, which often requires continuous external field driving, specific magnetic layers, or complex interface engineering, resulting in problems such as high Joule heating and limited energy efficiency. Chiral ferroelectric materials, with their chirality-dependent spin splitting, allow the electric field to manipulate the spin polarization of charge carriers, making them highly promising candidates for spin polarization. Importantly, the generation of spin photocurrents in chiral ferroelectrics provides an effective way to achieve non-volatile spin control beyond magnetic fields, demonstrating broad application prospects in spin optics and optoelectronics, igniting people's passion for exploration.

[0003] The circularly polarized photovoltaic effect is a unique second-order nonlinear photoelectric response of chiral materials, which can sensitively reflect the spin-splitting band structure characteristics of the material. Since circularly polarized light carries spin angular momentum, left-handed and right-handed circularly polarized light can selectively excite carriers with different spin orientations, thereby generating spin-polarized photocurrents with opposite directions. The direction of the photocurrent can be directly controlled by switching the helicity of the incident light. This provides a simple and efficient new method for the generation and manipulation of spin-polarized currents, and also opens up new directions for the characterization of chiral materials and their device applications.

[0004] However, the development of chiral spintronics still faces severe material bottlenecks. On the one hand, inorganic chiral semiconductor materials with large band-edge spin splitting are extremely scarce, making it difficult to meet the application requirements of high-performance devices. On the other hand, unlike organic ferroelectric materials containing chiral carbon atom centers, most inorganic ferroelectric materials do not possess chiral centers themselves. How to effectively introduce chirality into inorganic ferroelectric materials and achieve a large spin splitting effect has long been a key scientific problem that needs to be solved in the field of ferroelectric materials. Therefore, developing novel inorganic chiral ferroelectric semiconductor materials and constructing high-performance circularly polarized photodetectors based on them is of great scientific significance and application value for promoting the development of chiral spintronics. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure and its fabrication method. By utilizing the synergistic effect of the chiral geometry of the nanoisland and intrinsic spin splitting, the rotational selectivity response of circularly polarized light is significantly improved, providing a new low-power and simple structural solution for chiral spintronic devices.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0007] A circularly polarized photodetector based on a triangular ferroelectric nanoisland structure comprises a bottom electrode, a substrate, a ferroelectric layer, and a top electrode stacked from bottom to top. The substrate is an n-type semiconductor substrate doped with Nb-doped SrTiO3, the ferroelectric layer is an Eu-doped BiFeO3 thin film, and the Nb-doped SrTiO3 substrate and the Eu-doped BiFeO3 thin film form a pn heterojunction.

[0008] The Nb doping mass fraction in the Nb-doped SrTiO3 substrate is 0.5%-1.0%, preferably 0.7%.

[0009] The structural formula of the Eu-doped BiFeO3 is Bi 0.9 Eu 0.1 FeO3.

[0010] The thickness of the substrate is 0.3 mm to 1.0 mm, preferably 0.5 mm; the thickness of the ferroelectric layer is 50 nm to 150 nm, preferably 80 nm.

[0011] The thickness of the top electrode is 30nm-100nm, preferably 60nm; the thickness of the bottom electrode is 0.1mm-0.5mm, preferably 0.1mm-0.2mm.

[0012] The material of the top electrode is selected from at least one of Pt, Au, Ag, ITO, and FTO, preferably Pt; the material of the bottom electrode is selected from at least one of In, Ga, Al, Au, and Cu, preferably In.

[0013] A method for fabricating a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure includes the following steps:

[0014] (1) Using Eu-doped BiFeO3 as the target material, a ferroelectric layer was epitaxially grown on the surface of Nb-doped SrTiO3 substrate by pulsed laser deposition.

[0015] (2) A top electrode is deposited on the upper surface of the ferroelectric layer using physical vapor deposition technology;

[0016] (3) A bottom electrode is prepared on the lower surface of the Nb-doped SrTiO3 substrate to complete the fabrication of the circularly polarized photodetector.

[0017] In step (1), Bi 0.9 Eu 0.1 The FeO3 target material was prepared by solid-state reaction method, and the reaction raw materials were Bi2O3, Eu2O3 and Fe2O3 powders in corresponding proportions.

[0018] The growth parameters for pulsed laser deposition are as follows: growth temperature 600℃-750℃, preferably 660℃-680℃; growth oxygen pressure 5Pa-30Pa, preferably 15Pa; laser energy 200mJ-350mJ, preferably 260mJ-280mJ; laser frequency 1Hz-10Hz, preferably 3Hz; and target-to-substrate distance 4.0cm-6.0cm, preferably 5.0cm.

[0019] After pulsed laser deposition, the temperature is first cooled to 300℃-500℃ at an oxygen pressure of 0.5 atm-2 atm at a rate of 1℃ / min-5℃ / min, and then cooled to room temperature at a rate of 2℃ / min-10℃ / min; preferably, it is cooled to 400℃ at an oxygen pressure of 1 atm at a rate of 2℃ / min, and then cooled to room temperature at a rate of 4℃ / min.

[0020] The physical vapor deposition technique mentioned in step (2) is selected from at least one of magnetron sputtering, electron beam evaporation, and thermal evaporation; the bottom electrode mentioned in step (3) is prepared by welding, vapor deposition, or sputtering, preferably by welding.

[0021] The beneficial effects of this invention are:

[0022] (1) This invention constructs a pn heterojunction of Nb-doped SrTiO3 substrate and Eu-doped BiFeO3 film as a photosensitive element. The built-in electric field effectively suppresses dark current and promotes the separation and transport of photogenerated carriers, realizing self-driven detection without external bias voltage, thus fundamentally reducing device power consumption. At the same time, by controlling the lattice through Eu doping and combining it with pulsed laser deposition (PLD) process parameters, the controllable fabrication of self-assembled triangular ferroelectric nanoisland crystal arrays is realized. This three-dimensional nanostructure significantly enhances the interaction between light and matter, and the chiral geometry of the triangular nanoislands and the BEFO intrinsic chiral spin splitting effect work synergistically to significantly enhance the spin selectivity response of the device to circularly polarized light, greatly improving the sensitivity and response speed of the detector.

[0023] (2) The present invention is based on the intrinsic chirality of chiral ferroelectric materials to achieve the generation and control of spin polarization current. The device has a high sensitivity response to the rotation direction of circularly polarized light. The photocurrent direction can be directly reversed by switching the helicity of the incident light, providing a simple and efficient new way for the fully electronic control of spin polarization current.

[0024] (3) The device of the present invention adopts a simple stacked structure and has a mature fabrication process. It does not require complex micro-nano processing or special material synthesis equipment, which significantly reduces the fabrication cost and operation difficulty of the device. At the same time, the technical solution has good scalability. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the circularly polarized photoelectric detection system in an embodiment of the present invention.

[0027] Figure 2 This is a schematic diagram of the AFM of the BEFO triangular nanoisland array obtained in an embodiment of the present invention.

[0028] Figure 3 The curves showing the change of photocurrent with the quarter-wave plate rotation angle in this embodiment of the invention and the polarization-dependent photocurrent components obtained by fitting are shown. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] like Figure 1 As shown, the circularly polarized photodetector based on a triangular ferroelectric nanoisland structure of the present invention includes a photoelectric conversion element and a matching photoelectric measurement system and optical elements. The photoelectric conversion element is arranged in layers from bottom to top, consisting of a bottom electrode, a substrate, a ferroelectric layer, and a top electrode. The bottom electrode and the top electrode are electrically connected to the photoelectric measurement system, respectively.

[0031] The bottom electrode is an In electrode with a thickness of 0.1-0.2 mm; the substrate is a 0.7 wt% Nb-doped SrTiO3 (NSTO) single crystal substrate with a thickness of 0.5 mm; the ferroelectric layer is Bi. 0.9 Eu 0.1A self-assembled triangular nanoisland crystal array of FeO3 (BEFO) with a thickness of 80 nm is used; the top electrode is a Pt electrode with a thickness of 60 nm. The p-type BEFO ferroelectric semiconductor and the n-type NSTO substrate are used to construct a pn heterojunction, which serves as the core photosensitive element of the detector.

[0032] The optical elements include a 405nm wavelength laser emitter (with a focusing lens), a shutter, an attenuation filter, a polarizer, and a quarter-wave plate arranged sequentially. The laser emitted by the laser emitter passes through the above optical elements in sequence and is incident obliquely at a 45° angle onto the top electrode surface of the detector. The photoelectric measurement system uses a Keithley 2410 source meter for high-precision extraction and quantification of the photocurrent signal generated by the detector.

[0033] Example 1

[0034] A circularly polarized photodetector based on a triangular ferroelectric nanoisland structure, and the specific steps for fabricating the core photosensitive element in the circularly polarized photodetector are as follows:

[0035] (1) Preparation of BEFO ceramic target

[0036] High-purity Bi₂O₃ (99.99%), Eu₂O₃ (99.99%), and Fe₂O₃ (99.99%) oxide powders were used as raw materials, and the mixture was prepared according to a stoichiometric ratio of Bi₂O₃. 0.9 Eu 0.1 FeO3 was weighed and mixed, with Bi2O3 in excess by 10% to compensate for the volatilization of Bi during target sintering and film growth. The mixed powder was placed in a ball mill and ball-milled for 12 hours, dried, pre-fired at 880℃ for 1 hour, ball-milled again, and pressed into discs with a diameter of 25 mm and a thickness of 5 mm. Finally, it was sintered at 900℃ for 12 hours to obtain a dense BEFO ceramic target.

[0037] (2) Epitaxial growth of BEFO nanoisland array

[0038] BEFO thin films were epitaxially grown on NSTO single-crystal substrates using pulsed laser deposition (PLD) technology.

[0039] Substrate pretreatment: Select a single-sided polished NSTO (001) single crystal substrate with a specification of 3mm×3mm×0.5mm, and clean it by ultrasonication for 5 minutes each in acetone, anhydrous ethanol and deionized water. After drying with nitrogen, immediately send it into the PLD vacuum chamber.

[0040] PLD growth parameters: growth temperature 670℃, growth oxygen pressure 15Pa, laser energy 270mJ, laser frequency 3Hz, target-to-substrate distance 5.0cm, deposition time 60min.

[0041] Post-treatment cooling: After deposition, maintain an oxygen pressure of 1 atm, first cool to 400°C at a rate of 2°C / min, then allow to cool naturally to room temperature at a rate of 4°C / min to obtain the desired result. Figure 2 The self-assembled triangular BEFO ferroelectric nanoisland crystal array shown.

[0042] (3) Electrode preparation

[0043] A 60 nm thick Pt top electrode was deposited on the surface of the BEFO nanoisland array using magnetron sputtering technology; an 0.15 mm thick In bottom electrode was welded on the lower surface of the NSTO substrate using indium soldering technology to complete the fabrication of the detector device.

[0044] The performance of the circularly polarized photodetector prepared in Example 1 was tested using the following methods:

[0045] Building such Figure 1 The test system shown uses a diode semiconductor laser with a wavelength of 405 nm, a power of 100 mW, and a spot area of ​​5 mm² as the light source. The laser light passes sequentially through a shutter, an attenuation filter, a polarizer, and a quarter-wave plate before being incident at a 45° angle onto the surface of the Pt top electrode of the detector. With the sample stationary and the incident light intensity constant, the polarization state of the incident light is continuously adjusted by rotating the quarter-wave plate. The photocurrent signal is recorded every 5° starting from 0°, and no external bias voltage is required throughout the test.

[0046] When linearly polarized light passes through a quarter-wave plate, its polarization state undergoes a periodic transition from linearly polarized light to elliptically polarized light and then to circularly polarized light (left-handed / right-handed) as the plate rotates.

[0047] The total photocurrent generated by the detector can be decomposed using the following phenomenological formula:

[0048] ,in:

[0049] Where C represents the current induced by circularly polarized light excitation; L1 and L2 are the photocurrent components induced by the photocurrent effect and drag effect induced by linearly polarized light excitation, respectively; J0 represents the photocurrent component independent of polarization, which is induced by linearly polarized photovoltaic effect, photon drag effect, thermoelectric effect, photovoltaic effect and Danby effect, etc.

[0050] Test results are as follows Figure 3 As shown, the detector prepared by this invention can generate a significant photocurrent response under zero bias voltage, and the photocurrent intensity exhibits a significant periodic change with the rotation angle of the 1 / 4 waveplate, indicating that the device has different response sensitivities to left-handed and right-handed circularly polarized light, and successfully realizes the self-driven circularly polarized light detection function.

[0051] Example 2

[0052] A circularly polarized photodetector based on a triangular ferroelectric nanoisland structure, and the specific steps for fabricating the core photosensitive element in the circularly polarized photodetector are as follows:

[0053] (1) Preparation of BEFO ceramic target

[0054] High-purity Bi₂O₃ (99.99%), Eu₂O₃ (99.99%), and Fe₂O₃ (99.99%) oxide powders were used as raw materials, and the mixture was prepared according to a stoichiometric ratio of Bi₂O₃. 0.9 Eu 0.1 FeO3 was weighed and mixed, with Bi2O3 in excess by 10% to compensate for the volatilization of Bi during target sintering and film growth. The mixed powder was placed in a ball mill and ball-milled for 12 hours, dried, pre-fired at 880℃ for 1 hour, ball-milled again, and pressed into discs with a diameter of 25 mm and a thickness of 5 mm. Finally, it was sintered at 900℃ for 12 hours to obtain a dense BEFO ceramic target.

[0055] (2) Epitaxial growth of BEFO nanoisland array

[0056] BEFO thin films were epitaxially grown on NSTO single-crystal substrates using pulsed laser deposition (PLD) technology.

[0057] Substrate pretreatment: A single-sided polished NSTO (001) single crystal substrate with a specification of 3mm×3mm×0.3mm was selected, with Nb doping amount of 0.5wt%. It was ultrasonically cleaned for 5 minutes each in acetone, anhydrous ethanol and deionized water, and then dried with nitrogen and immediately sent into the PLD vacuum chamber.

[0058] PLD growth parameters: growth temperature 600℃, growth oxygen pressure 5Pa, laser energy 200mJ, laser frequency 1Hz, target-to-substrate distance 4.0cm, deposition time 60min, resulting in a BEFO film with a thickness of approximately 50nm.

[0059] Post-processing cooling: After deposition, maintain an oxygen pressure of 0.5 atm, first cool to 300°C at a rate of 1°C / min, and then naturally cool to room temperature at a rate of 2°C / min to obtain a self-assembled triangular BEFO ferroelectric nanoisland crystal array.

[0060] (3) Electrode preparation

[0061] An Au top electrode with a thickness of 30 nm was deposited on the surface of the BEFO nanoisland array using electron beam evaporation technology; an Al bottom electrode with a thickness of 0.2 mm was deposited on the lower surface of the NSTO substrate using thermal evaporation, thus completing the fabrication of the detector device.

[0062] Example 3

[0063] A circularly polarized photodetector based on a triangular ferroelectric nanoisland structure, and the specific steps for fabricating the core photosensitive element in the circularly polarized photodetector are as follows:

[0064] (1) Preparation of BEFO ceramic target

[0065] High-purity Bi₂O₃ (99.99%), Eu₂O₃ (99.99%), and Fe₂O₃ (99.99%) oxide powders were used as raw materials, and the mixture was prepared according to a stoichiometric ratio of Bi₂O₃. 0.9 Eu 0.1 FeO3 was weighed and mixed, with Bi2O3 in excess by 10% to compensate for the volatilization of Bi during target sintering and film growth. The mixed powder was placed in a ball mill and ball-milled for 12 hours, dried, pre-fired at 880℃ for 1 hour, ball-milled again, and pressed into discs with a diameter of 25 mm and a thickness of 5 mm. Finally, it was sintered at 900℃ for 12 hours to obtain a dense BEFO ceramic target.

[0066] (2) Epitaxial growth of BEFO nanoisland array

[0067] BEFO thin films were epitaxially grown on NSTO single-crystal substrates using pulsed laser deposition (PLD) technology.

[0068] Substrate pretreatment: A single-sided polished NSTO (001) single crystal substrate with a specification of 3mm×3mm×1mm was selected, with Nb doping amount of 1.0wt%. It was ultrasonically cleaned for 5 minutes each in acetone, anhydrous ethanol and deionized water, and then dried with nitrogen and immediately sent into the PLD vacuum chamber.

[0069] PLD growth parameters: growth temperature 750℃, growth oxygen pressure 30Pa, laser energy 350mJ, laser frequency 7Hz, target-to-substrate distance 6.0cm, deposition time 30min, resulting in a BEFO film with a thickness of approximately 150nm.

[0070] Post-processing cooling: After deposition, maintain an oxygen pressure of 2 atm, first cool to 500°C at a rate of 5°C / min, and then naturally cool to room temperature at a rate of 10°C / min to obtain a self-assembled triangular BEFO ferroelectric nanoisland crystal array.

[0071] (3) Electrode preparation

[0072] A 100 nm thick ITO top electrode was deposited on the surface of the BEFO nanoisland array using thermal evaporation technology; a 0.2 mm thick Cu bottom electrode was sputtered on the lower surface of the NSTO substrate using magnetron sputtering to complete the fabrication of the detector device.

[0073] Example 4

[0074] A circularly polarized photodetector based on a triangular ferroelectric nanoisland structure, and the specific steps for fabricating the core photosensitive element in the circularly polarized photodetector are as follows:

[0075] (1) Preparation of BEFO ceramic target

[0076] High-purity Bi₂O₃ (99.99%), Eu₂O₃ (99.99%), and Fe₂O₃ (99.99%) oxide powders were used as raw materials, and the mixture was prepared according to a stoichiometric ratio of Bi₂O₃. 0.9 Eu 0.1 FeO3 was weighed and mixed, with Bi2O3 in excess by 10% to compensate for the volatilization of Bi during target sintering and film growth. The mixed powder was placed in a ball mill and ball-milled for 12 hours, dried, pre-fired at 880℃ for 1 hour, ball-milled again, and pressed into discs with a diameter of 25 mm and a thickness of 5 mm. Finally, it was sintered at 900℃ for 12 hours to obtain a dense BEFO ceramic target.

[0077] (2) Epitaxial growth of BEFO nanoisland array

[0078] BEFO thin films were epitaxially grown on NSTO single-crystal substrates using pulsed laser deposition (PLD) technology.

[0079] Substrate pretreatment: A single-sided polished NSTO (001) single crystal substrate with a specification of 3mm×3mm×1.0mm was selected, with Nb doping amount of 1.0wt%. It was ultrasonically cleaned for 5min each in acetone, anhydrous ethanol and deionized water, and then dried with nitrogen and immediately sent into the PLD vacuum chamber.

[0080] PLD growth parameters: growth temperature 700℃, growth oxygen pressure 20Pa, laser energy 300mJ, laser frequency 5Hz, target-to-substrate distance 5.5cm, deposition time 30min, resulting in a BEFO film with a thickness of approximately 80nm.

[0081] Post-processing cooling: After deposition, maintain an oxygen pressure of 1.5 atm, first cool to 450°C at a rate of 3°C / min, and then naturally cool to room temperature at a rate of 6°C / min to obtain a self-assembled triangular BEFO ferroelectric nanoisland crystal array.

[0082] (3) Electrode preparation

[0083] A 70 nm thick Ag top electrode was deposited on the surface of the BEFO nanoisland array using magnetron sputtering technology; a 0.2 mm thick Ga bottom electrode was welded on the lower surface of the NSTO substrate using gallium bonding technology to complete the fabrication of the detector device.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A circularly polarized photodetector based on a triangular ferroelectric nanoisland structure, comprising a bottom electrode, a substrate, a ferroelectric layer, and a top electrode stacked sequentially from bottom to top, characterized in that... The substrate is an Nb-doped SrTiO3 substrate, the ferroelectric layer is an Eu-doped BiFeO3 thin film, and the Nb-doped SrTiO3 substrate and the Eu-doped BiFeO3 thin film form a pn heterojunction.

2. The circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 1, characterized in that, The Nb doping concentration in the Nb-doped SrTiO3 substrate is 0.5-1.0 wt%; the chemical formula of the Eu-doped BiFeO3 is Bi. 0.9 Eu 0.1 FeO3.

3. The circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 2, characterized in that, The substrate has a thickness of 0.3-1 mm; the ferroelectric layer has a thickness of 50-150 nm.

4. The circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 3, characterized in that, The thickness of the top electrode is 30-100 nm, and the thickness of the bottom electrode is 0.1-0.5 mm.

5. The circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 4, characterized in that, The material of the top electrode is any one or two or more of Pt, Au, Ag, ITO and FTO, and the material of the bottom electrode is any one or two or more of In, Ga, Al, Au and Cu.

6. The method for fabricating a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Using Eu-doped BiFeO3 as the target material, a ferroelectric layer was epitaxially grown on the surface of Nb-doped SrTiO3 substrate by pulsed laser deposition. (2) A top electrode is deposited on the upper surface of the ferroelectric layer using physical vapor deposition technology; (3) A bottom electrode is prepared on the lower surface of the Nb-doped SrTiO3 substrate to complete the fabrication of the circularly polarized photodetector.

7. The method for fabricating a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 6, characterized in that, In step (1), Bi 0.9 Eu 0.1 The FeO3 target material was prepared by solid-state reaction method, and the reaction raw materials were Bi2O3, Eu2O3 and Fe2O3 powders in corresponding proportions.

8. The method for fabricating a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 7, characterized in that, The growth parameters for pulsed laser deposition are: growth temperature 600℃-750℃, growth oxygen pressure 5Pa-30Pa, laser energy 200mJ-350mJ, laser frequency 1Hz-10Hz, and target-to-substrate distance 4.0cm-6.0cm.

9. The method for fabricating a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 8, characterized in that, After pulsed laser deposition, the temperature is first cooled to 300℃-500℃ at an oxygen pressure of 0.5 atm-2 atm at a rate of 1℃ / min-5℃ / min, and then cooled to room temperature at a rate of 2℃ / min-10℃ / min.

10. The method for fabricating a circularly polarized photodetector based on a triangular ferroelectric nanoisland structure according to claim 6, characterized in that, In step (2), the physical vapor deposition technique is selected from at least one of magnetron sputtering, electron beam evaporation, and thermal evaporation; in step (3), the bottom electrode is prepared by welding, vapor deposition, or sputtering.